Evaluation des Journées de Santé de l’Enfant dans la Zone de Santé Rurale de Basoko en 2016, RD Congo. - Salomon OTOWANGE MANDEFU (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
We led a survey in 21 Aires of Health of the Zone of Farming Health of Basoko whose objective was to value the Days of Health of the child in 2016. The last organized to the provincial Division of the health of the Tshopo in Democratic Republic of Congo. The survey was descriptive. We recommended the method of audit of the Quality of the data and Benchmarkings. The following results have been gotten: vaccinal covers in VPO3 (102%), proportion of children recovered in VPO3 the month of organization of the Days of Health of the child (15,8%) against 19,8% in DTC-HepB-Hib3, 11 areas of health (52,3%) didn’t reach the objective of supplémenter 80% of children of 6 to 59 months and déparasiter those of 12 to 59 months, indication of quality aggregated of the data of vaccination gotten was from 49% to the Centers of Health and 46% to the Central Office of the Health Zone, cost-efficiency ratio of the activities of Days of Health of the child has been valued to 46% to the Central Office of the Health Zone against 49% to the Centers of Health. Thus, the coupling" Days of Health of the child and recuperation of children of 0 to 11 months and the pregnant women" is an approach that the beneficiaries of vaccination service must perpetuate in order to improve their vaccinal covers by antigen. This one asks for an update of tools of routine vaccination management traditionally used.